The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1126/science.285.5424.81
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Detection of Hydrogen Trioxide

Abstract: Hydrogen trioxide (HO3) has long been postulated as a key intermediate in important atmospheric processes but has proved difficult to detect. The molecule was unequivocally detected in experiments based on neutralization-reionization and neutralization-reionization/collisionally activated dissociation mass spectrometry, using protonated ozone (HO3+) as the charged precursor. Hydrogen trioxide is a relatively stable species and has a H-O-O-O connectivity and a lifetime exceeding 10(-6) seconds at ambient temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 26 publications
(24 reference statements)
4
85
0
2
Order By: Relevance
“…The hydrotrioxide radical has been postulated to be an important intermediate in atmospheric processes (16), but it was not clear whether after formation it would dissociate immediately into 3 O 2 and HO • (17,18). However, HO 3 • has recently been detected experimentally by both Speranza (19) and Cacace and coworkers (20,21) using Fourier-transform ion cyclotron resonance mass spectrometry and neutralizationreionization mass spectrometry, respectively, and its lifetime has been calculated to be of the order of microseconds. Our own qualitative chemical reasoning as well as quantum chemical calculations point to the potential of the HO 3 • or the [HO 2…”
Section: Resultsmentioning
confidence: 99%
“…The hydrotrioxide radical has been postulated to be an important intermediate in atmospheric processes (16), but it was not clear whether after formation it would dissociate immediately into 3 O 2 and HO • (17,18). However, HO 3 • has recently been detected experimentally by both Speranza (19) and Cacace and coworkers (20,21) using Fourier-transform ion cyclotron resonance mass spectrometry and neutralizationreionization mass spectrometry, respectively, and its lifetime has been calculated to be of the order of microseconds. Our own qualitative chemical reasoning as well as quantum chemical calculations point to the potential of the HO 3 • or the [HO 2…”
Section: Resultsmentioning
confidence: 99%
“…(13) and (14) with β = 0, (αl + x) replaced with 1, and х 2 replaced with х. Note that, if in Scheme 4 chain initiation via reaction 1 is due to the interaction between molecular hydrogen and molecular oxygen yielding the hydroxyl radical НО • instead of Н • atoms and if this radical reacts with an oxygen molecule (reaction 4) to form the hydrotrioxyl radical 3 HO  (which was obtained in the gas phase by neutralization reionization (NR) mass spectrometry [83] and has a lifetime of >10 -6 s at 298 K) and chain termination takes place via HO  , respectively, the expressions for the water chain formation rates derived in the same way will appear as a rational 14 For example, the ratio of the rate constants of the bimolecular disproportionation and dimerization of free radicals at room temperature is k(HO • + HO2 • )/2k(2HO • )2k(2HO2 • ) 0.5 = 2.8 in the atmosphere [92] and k(H • + HO • )/2k(2H • )2k(2HO • ) 0.5 = 1.5 in water [94]. These values that are fairly close to unity.…”
Section: Methodsmentioning
confidence: 99%
“…The O4 molecule was identified by NR mass spectrometry [74]. assumption about the cyclic structure of the 4 HO  radical can stem from the fact that its mean lifetime in water at 294 K, which is (3.6 ± 0.4) × 10 -5 s (as estimated [66] HO  radical [68,83] estimated in the same way [66] for the same conditions [84], (9.1 ± 0.9) × 10 -6 s. MP2/6-311++G** calculations using the Gaussian-98 program confirmed that the cyclic structure of 4 HO  [85] is energetically more favorable than the helical structure [68] (the difference in energy is 4.8-7.3 kJ mol -1 , depending on the computational method and the basis set). 11 For example, with the MP2(full)/6-31G(d) method, the difference between the full energies of the cyclic and acyclic HO  can exist in both forms, but the cyclic structure is obviously dominant (87%, K eq = 6.5) [85].…”
Section: Methodsmentioning
confidence: 99%
“…Ozone does not interact with molecular hydrogen. At moderate temperatures, it decomposes fairly slowly, particularly in the presence of O 2 (X 3 Σ − g ) [70]. The reaction of ozone with H • atoms, which is not impossible, results in their replacement with HO • radicals.…”
Section: Addition Of the Hydrogen Atommentioning
confidence: 99%
“…The formation rates of the stable products of nonchain oxidation (k 3 = 0), provided that either reactions (2) and (4) or reaction (2) alone (k 4 = 0) occurs (Scheme 4; in the latter case, reactions (6) and (7) Note that, if in Scheme 4 chain initiation via reaction (1) is due to the interaction between molecular hydrogen and molecular oxygen yielding the hydroxyl radical HO • instead of H • atoms and if this radical reacts with an oxygen molecule (reaction (4)) to form the hydrotrioxyl radical HO • 3 (which was obtained in the gas phase by neutralization reionization (NR) mass spectrometry [70] and has a lifetime of >10 −6 s at 298 K) and chain termination takes place via reactions (5)- (7) involving the HO • and HO • 3 , radicals instead of H • and HO • 4 , respectively, the expressions for the water chain formation rates derived in the same way will appear as a rational function of the oxygen concentration x without a maximum:…”
Section: Addition Of the Hydrogen Atommentioning
confidence: 99%